Effect of Differential Speed Rolling Temperature into Mechanical Properties of AZ31B Magnesium Alloy - Azal R. Ismail; Emad A. Hussein (Engineering and Technology Journal, 2016)
The received AZ31B magnesium alloy sheets of 2 mm in thickness were subjected to differential speed rolling (DSR) process performed on a mill, of which the rotation speed ratio of the lower roll and upper one is kept at constant 1.15, by using the different upper and lower roller diameters. The influence of the rolled sheet temperature on the microstructure of the specimens was examined by optical microscopy, and elongation-to-failure of tensile test at temperature 623 K and initial strain-rate range between 0.5×10-3 - 1.83×10-3 s-1 was measured. The present process was found to be effective to refine the grain size. Grain refinement became more marked and uniform. The sheet DSRed at 473K exhibited the highest values of 340% and 0.35 for elongation-to-failure and strain rate sensitivity (m) respectively.